Draft Genome Sequence of Listeria monocytogenes CIIMS-NV-3, a Strain Isolated from Vaginal Discharge of a Woman from Central India - Kishnani, Pooja M. (Microbiol Resour Announc, 2019)
We present here the draft genome sequence of Listeria monocytogenes CIIMS-NV-3, a serovar 4b strain isolated from the vaginal swab of a female patient from central India. The availability of this genome may provide useful information on virulence characteristics for comparative genomic analysis.